Depositional facies and sequence architecture of the Yijianfang Formation in the Shuntuoguole Low Uplift, Tarim Basin, NW China. Issue 8 (27th April 2022) - Yu, Jinxin; Song, Yanchen; Shi, Kaibo; Chen, Senran; Wang, Qiqi; Liu, Bo; Han, Jun
Abstract : In the Middle Ordovician, a ramp carbonate platform was developed in the Shuntuoguole Low Uplift, Tarim Basin. The depositional facies and sequence stratigraphy were investigated using petrographic observations and Fischer plot analyses to clarify the evolution and distribution of depositional facies within the sequence stratigraphic framework of the Yijianfang Formation. Nine types of microfacies (MF1–MF9) were identified in seven environments on a ramp: (a) peritidal, (b) lagoon, (c) low‐energy bioclastic shoal, (d) shoal, (e) sheltered proximal middle‐ramp, (f) low‐energy bioclastic shoal middle‐ramp, and (g) shoal middle‐ramp. A depositional model was established based on analyses of the depositional facies from the key wells. Fischer plots obtained based on fourth‐order cycles identified from continuous wavelet transform of gamma‐ray logging data were analysed. The results show that the changes in relative sea level, as indicated by Fischer plots, are highly consistent with the evolution of paleo‐water depths indicated by microfacies types, microfacies associations, and geochemical indicators. Four third‐order depositional sequences (SQ1–4) were identified according to variations in accommodation space. The accommodation space and its growth rate during the SQ2 transgressive period were the largest, it manifested as rapid landward migration of facies, and sudden changes in the gamma‐ray logging values at the maximum flooding surface. This feature can be easily compared across the entire region. The results of this study indicate that changes in relative sealevel in the Yijianfang Formation are consistent with the global sea‐level change curve, which suggests that sea‐level fluctuation is the main factoir controlling sequence architecture and the evolution of depositional facies. Abstract : Sea‐level changes in the study area were reconstructed based on percent stacked bar charts of microfacies, Fischer plots obtained based on fourth‐order cycles identified by continuous wavelet transform of gamma‐ray logging data, and geochemical indicators. These three indicators of sea‐level change are consistent. Based on the changes in the accommodation space, four third‐order sequences (SQ1–4) were identified in the Yijianfang Formation, Tarim Basin. The time‐dependent evolution of depositional facies within a sequence stratigraphic framework was deciphered. The comparison of Fischer plots with the coeval global sea‐level change curve showed that sea‐level change was the main factor controlling sequence architecture and sedimentary infilling.